Profile and social features concerning family caregivers in a traumatology and rehabilitation hospital - Aurora Quero Rufián; Rafael Briones Gómez; María Ángeles Prieto Rodríguez; Adela Navarro López; Nuria Pascual Martínez; Carmen Guerrero Ruiz (Fundación para el Desarrollo de la Enfermería, 2004)
Studies on family care giving within hospitals are not frequent. This situation contributes to make these people underconsidered by the health system. The aim of this study is to analyze the profile of family caregivers, the needs they attend and how they are considered by the health professionals in a traumatology and rehabilitation hospital.Methodology: Descriptive and cross-sectional study, which included one hundred interviews performed between September and October 2002 in traumatology, maxillofacial surgery, neurology, and neurosurgery wards. Results: The family caregiver profile corresponds to a female with a median age of 48 years who spends a mean of 20 hours per day in the hospital. Surveillance and company were the main contributions to the patient care according to caregivers' answers. Conclusions: Wives or mothers become the main family caregivers. Their contribution implies monetary and time costs as well as physic, psychological and social impact. The care offered by the family caregivers is scarcely supported by professional help. Increasing the professionals' recognition of the family caregivers is a social requirement.